2018
DOI: 10.2147/copd.s168772
|View full text |Cite
|
Sign up to set email alerts
|

<em>ACE</em> gene polymorphism is associated with COPD and COPD with pulmonary hypertension: a meta-analysis

Abstract: PurposeAngiotensin-converting enzyme (ACE) gene I/D polymorphism has been studied in relation to the susceptibility to COPD and COPD with pulmonary hypertension (PH) with inconclusive results. We performed the first comprehensive meta-analysis to evaluate accurately the association between the ACE gene polymorphism and the risk of COPD.MethodsData were analyzed using odds ratios (ORs) and the corresponding 95% CIs to measure the strength of the models. Subgroup analyses were conducted by ethnicity and complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…The data were drawn from systematic reviews and meta analyses published in the past 15 years (since 2005) examining ACE genotypes and risk of cardiovascular, respiratory, diabetes, renal and stroke diseases. 8 , 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 Published studies in English which contained the largest cohort of patients were selected to represent each country. For countries where ACE genotype data were not available from systematic reviews and meta-analyses, further searching was conducted through PubMed and Google Scholar, using search terms ‘ACE polymorphisms + (country name)’ or ‘ACE genotype + (country name)’.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were drawn from systematic reviews and meta analyses published in the past 15 years (since 2005) examining ACE genotypes and risk of cardiovascular, respiratory, diabetes, renal and stroke diseases. 8 , 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 Published studies in English which contained the largest cohort of patients were selected to represent each country. For countries where ACE genotype data were not available from systematic reviews and meta-analyses, further searching was conducted through PubMed and Google Scholar, using search terms ‘ACE polymorphisms + (country name)’ or ‘ACE genotype + (country name)’.…”
Section: Methodsmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID- 19), caused by SARS-CoV2 virus, has evolved rapidly into a pandemic, with total confirmed cases of nearly 9 million, and more than 460,0 0 0 deaths worldwide as of 22 June 2020. 1 The COVID-19 fatality rates vary greatly across countries, and have been attributed to multiple factors including availability of healthcare resources and mitigation strate-The ACE gene is known to consist of two variant alleles; insertion (I) and deletion (D) polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review with meta-analysis of 15 studies (2635 participants, 288 participants of the PHT subgroup) showed that ACE gene polymorphism, particularly the homozygote variant, was associated with an increased risk of PHT in Asian COPD patients. 79 These results, however, should be validated in larger sample populations and in more ethnicities.…”
Section: Systematic Reviews and Meta-analysismentioning
confidence: 95%
“…4 PHT is present in more than 25% and 50% of the patients with moderate-to-severe COPD, and the 5-year survival of patients suffering PHT is almost half of patients without PHT (36% and 62%, respectively). 78,79 Furthermore, signs of elevated pulmonary artery pressure are associated with more frequent exacerbation episodes. In the meta-analysis of Chen et al of the risk of cardiovascular comorbidity in COPD, the odds of patients with COPD having diseases of pulmonary circulation were 5.14 times higher as compared to matched controls without COPD.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…The ACE gene produces the protein ACE, which converts angiotensin (AngI) into angiotensin II (AngII), a potent vasoactive peptide that leads to effects mainly hypertensive, highlighting its role in the physiology of blood vessels and inflammation [5,8]. Indeed, higher plasma levels of ACE have been reported when the D allele was present [5], accordingly, the ACE DD genotype has been established as an independent risk factor of CVD and hypertension [6,9]. Similarly, a recent meta-analysis [10] has shown a higher risk of hypertrophic cardiomyopathy in the DD genotype than in the II genotype; therefore, a protective effect against CVD risk can be attributed to the II genotype.…”
Section: Introductionmentioning
confidence: 99%